Study of Retanning Behaviour of Sulfonated Succinic Dihydrazide Formaldehyde Condensates Under Different Reactant Conditions - Saleem, Rashid; Adnan, Ahmad; Riaz, Muhammad; Hanif, Muhammad; Ashraf Qureshi, Fahim (Asian Journal of Chemistry, 2013)
Sulfonated succinic dihydrazide resins were prepared by controlled reaction of succinic dihydrazide, formaldehyde and sodium metabisulfite, through a three steps reaction. Sodium metabisulfite/succinic dihydrazide (S/SDH) mole ratio were varied from 0.1 to 0.4 mol and formaldehyde/succinic dihydrazide (F/SDH) molar ratio ranges from 2 to 5 mol. The effects on the fluidity and viscosity of resin solutions were observed with varying degree of sulfonation and formaldehyde/succinic dihydrazide mole ratio. Viscosity of resin solutions increase with increasing formaldehyde/succinic dihydrazide ratio and decreased with increasing sodium metabisulfite/succinic dihydrazide ratio. The viscosity of the resin solutions increase with increasing molecular weight of polymer, until a critical molecular weight, at which point, gelation of resins occur. The resins were applied on chrome tanned leather and their influences were studied as retanning agent against commercial sulfonated melamine formaldehyde powder resin (Resin N. 2). Tear strength, tensile strength and elongation at break of retanned leathers were measured. Optical images and TGA were used to evaluate the fiber surface texture of leather and thermal stability of resins, respectively. FT-IR and proton NMR techniques were used to characterize the functionalities of the resin.